Implementation of Encryption Algorithm for Data Security in Cloud Computing (International Journal of Advanced Research in Computer Science, 2017)
Cloud computing is the present technology which is gaining greater attentions. Nowadays, among all the technologies that includes the network security, data protections, virtualization security, application integrity and identity management, the cloud is the most essential and key aspect. Among all the above mentioned issues, data protection is one of the most important security element because organizations cannot transfer their data to the remote machines as there is no guarantee of data protection by the cloud service providers. Many techniques are already available to protect the data in cloud. Though there are many number of techniques implemented to have focus on security of data but still some challenges persist. Cloud computing solves not only the computing problems but also caters loads of data with software updates etc. The user will be confident in utilising the cloud sources only if there is an appropriate collaboration between cloud client and cloud service provider. The most popular security techniques include SSL (Secure Socket Layer) Encryption, Algorithms like AES, Blowfish, DES, RSA, Cloud Computing, and Data Security. This paper mainly focus on how to analyse and evaluate the most important security encryption algorithms for data protection in cloud computing. Furthermore, this paper also discusses about some of the new security techniques for data protection which will be recommended in order to have improved security in cloud computing.Keywords: Cloud, Data Protection, Security, Asymmetric Algorithms, Symmetric Algorithm.